(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Analysis of the Impact of Market Segmentation on Local Fruit Purchase Decissions at Freshindo Sanglah. Market segmentation is the process of dividing a market into different groups to assist companies in determining appropriate marketing strategies and developing products or services that better align with consumer needs. This study aims to analyze the influence of geographic, demographic, psychographic, and behavioral market segmentation on local fruit purchase decisions at Freshindo Sanglah. The research employs interviewing, documentation, literature studies, and questionnaires for data collection and structural equation modeling with partial least squares (SEM-PLS) methodology for analysis. Test results indicate that geographical and behavioral segments partially and significantly impact purchasing decission, while demographic and psychographic segments are not significant. Recommendations that can be given is expanding online sales opportunities, diversifying local fruits offerings to compete against imported ones, and promoting the benefits and uniqueness of local produce to increase consumer awareness.